Arts-Based Approaches to Languages Education with Refugee-Background Learners in the Early Years: Co-Creating Spaces of Hope - Rachel Burke; Rebecca Soraya Field (MDPI AG, 2023)
Young learners with refugee experiences face a constellation of challenges particular to forced migration and resettlement. Experiences of trauma, violence, poverty, and disrupted or limited access to formal education and healthcare can have complex and long-term impacts on learning. Further, the sociocultural and linguistic challenges of undertaking education in unfamiliar schooling systems in transit and resettlement countries can also impede learner engagement and obscure individual strengths. However, like all student cohorts, children with refugee and asylum seeker backgrounds are also unique, with individual personal, sociocultural, and linguistic attributes on which to draw. While these assets may be overlooked or obscured in traditional educational contexts, arts-based approaches to instruction can offer generative and affirming learning spaces that illuminate individual strengths and provide powerful rejoinders to deficit constructions. This article provides an overview of recent research that explores vibrant and innovative arts-based approaches to languages instruction for refugee and asylum-seeker background learners in the early years. The article takes the form of a scoping study of literature using Arksey and O'Malley's framework to map the field of research, document novel instructional approaches, and identify key themes. Our discussion is oriented toward educators who seek to innovate their own instructional practice. In addition to exploring the creative avenues for language instruction described in the literature, we consider key themes that emerged inductively from our analysis including the agentic value of arts-based instructional practices, the role of narrative in articulating experiences of place and identities, and the significance of arts-based connections between home and school linguistic repertoires.